Biosynthesis of Silver Nanoparticles Mediated by Entomopathogenic Fungi: Antimicrobial Resistance, Nanopesticides, and Toxicity - Tárcio S. Santos; Tarcisio M. Silva; Juliana C. Cardoso; Ricardo L. C. de Albuquerque-Júnior; Aleksandra Zielinska; Eliana B. Souto; Patrícia Severino; Marcelo da Costa Mendonça (MDPI AG, 2021)
Silver nanoparticles are widely used in the biomedical and agri-food fields due to their versatility. The use of biological methods for the synthesis of silver nanoparticles has increased considerably due to their feasibility and high biocompatibility. In general, microorganisms have been widely explored for the production of silver nanoparticles for several applications. The objective of this work was to evaluate the use of entomopathogenic fungi for the biological synthesis of silver nanoparticles, in comparison to the use of other filamentous fungi, and the possibility of using these nanoparticles as antimicrobial agents and for the control of insect pests. In addition, the in vitro methods commonly used to assess the toxicity of these materials are discussed. Several species of filamentous fungi are known to have the ability to form silver nanoparticles, but few studies have been conducted on the potential of entomopathogenic fungi to produce these materials. The investigation of the toxicity of silver nanoparticles is usually carried out in vitro through cytotoxicity/genotoxicity analyses, using well-established methodologies, such as MTT and comet assays, respectively. The use of silver nanoparticles obtained through entomopathogenic fungi against insects is mainly focused on mosquitoes that transmit diseases to humans, with satisfactory results regarding mortality estimates. Entomopathogenic fungi can be employed in the synthesis of silver nanoparticles for potential use in insect control, but there is a need to expand studies on toxicity so to enable their use also in insect control in agriculture.